2019
DOI: 10.1016/j.jaci.2019.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells drive IgE-mediated disease but might be bystanders in many other inflammatory and neoplastic conditions

Abstract: Mast cells (MCs) are capable of executing powerful inflammatory response programs triggered by surface IgE cross-linking or through pattern recognition receptors. The question of how MCs contribute to human disease has been intensely investigated and stimulated much controversy. Correlative evidence comes from human studies, pointing to pathogenetic or protective MC functions in patients with atopic conditions, autoimmune disorders, type 2 diabetes, chronic urticaria, mastocytosis, and cancer. Experiments in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 227 publications
(272 reference statements)
0
17
0
Order By: Relevance
“…MCs are key initiators and modulators of allergic disorders, such as bronchial asthma, allergic rhinitis, urticaria, food allergies, anaphylaxis, atopic dermatitis, and angioedema [ 4 , 18 ]. As a result of their location, surface receptors, and a wide spectrum of inflammatory and immunomodulatory mediators, MCs are thought to act as the first sentinels in response to metabolic and immunological changes [ 19 22 ].…”
Section: Mcs Origin and Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCs are key initiators and modulators of allergic disorders, such as bronchial asthma, allergic rhinitis, urticaria, food allergies, anaphylaxis, atopic dermatitis, and angioedema [ 4 , 18 ]. As a result of their location, surface receptors, and a wide spectrum of inflammatory and immunomodulatory mediators, MCs are thought to act as the first sentinels in response to metabolic and immunological changes [ 19 22 ].…”
Section: Mcs Origin and Functionsmentioning
confidence: 99%
“…From being known for their detrimental role in allergic diseases, such as food allergies, asthma, and anaphylaxis, for decades; to now recognized as crucial players in a diverse array of physiological and pathologic functions, including vasodilation, angiogenesis, lymphangiogenesis, pathogen elimination, innate and adaptive immune responses, wound healing, and homeostasis. Moreover, MCs play an important role in many diseases, such as gastrointestinal disorders, diabetes, malignancies, and cardiovascular diseases [3][4][5][6]. However, to this day, the pathophysiological roles of MCs are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the skies are not all sunny in MC land, as Maurer et al 8 lament. Innovative and new MC-deficient mouse models have disputed some involvement in pathologies that had been assigned to MCs previously, such as experimental autoimmune encephalomyelitis (a model of multiple sclerosis) or rheumatoid arthritis.…”
Section: Mcs As Drivers Of Diseasementioning
confidence: 97%
“…Mast cells are involved in the pathological process of various allergic diseases [48], autoimmune diseases [93] and cancers [94]. Previous studies have shown that mast cell-derived IL-9 can promote susceptibility to IgEmediated experimental food allergy [50].…”
Section: Mast Cells In Tumor Immunitymentioning
confidence: 99%
“…In the presence of TGF-β and IL-15, Vδ2 T cells stimulated by antigens will produce a large amount of IL-9, which plays an important role in Vδ2 T cell-mediated antitumor immunity [45]. Mast cells are widely distributed around the microvasculature under the skin and visceral mucosa [46,47], and participate in allergic diseases by secreting a variety of cytokines [48,49]. In the intestinal mucosa, IL-9-producing mucosal mast cells (MMC9s) can promote food allergy mediated by IgE [50].…”
Section: Introductionmentioning
confidence: 99%